Biofortification of black chickpea (Cicer arietinum L.) through plant growth-promoting rhizobacteria: enhancing nutritional and bioactive compounds - Hilal YILMAZ (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
The chickpea (Cicer arietinum L.), often called the “poor man’s meat”, is a legume with remarkable nutritional value. Recently, its recognition as a functional food has grown, owing to its ability to improve human nutrition and reduce disease risk. This study explores the biofortification potential of black chickpea seeds through the targeted application of Bacillus subtilis, B. megaterium, and Rhizobium cicer. By inoculating the seeds, these rhizobacterial treatments aim to naturally enhance the bioactive compound profile by manipulating the plant root systems. The study comprehensively assesses key parameters including total antioxidant activity, protein content, total phenolic content, and macro- and micronutrient composition of bacterial inoculated black chickpeas grown under the ecological conditions of Bolu, Türkiye. Results showed that rhizobacterial inoculation significantly improved all measured traits compared to the control group. B. subtilis treatment increased total antioxidant activity by 10.6% and total phenolic content by 19.5%. Protein content exhibited by approximately 11% across all treatments. R. cicer treatment led to the most pronounced increases in macro- and micronutrients, particularly in calcium (38.5%), potassium (82.7%), magnesium (26.35%), phosphorus (15.23%), iron (155.3%), and zinc (44.21%). These results demonstrate that rhizobacterial treatments can significantly enhance black chickpeas’ biochemical and nutritional quality. Thus, biofortified black chickpeas offer a promising, sustainable strategy for addressing global micronutrient deficiencies and combating hidden hunger, providing a valuable tool for improving food security.